2017
DOI: 10.1002/art.39987
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B Irradiation Causes Stimulator of Interferon Genes–Dependent Production of Protective Type I Interferon in Mouse Skin by Recruited Inflammatory Monocytes

Abstract: Objective Photosensitivity is common in patients with systemic lupus erythematosus, although the mechanisms linking ultraviolet (UV) light to flares are not well understood. We undertook this study to determine whether repetitive UVB exposure could induce type I interferon (IFN) production in normal mouse skin, and to investigate the roles of inflammatory monocytes and plasmacytoid dendritic cells (PDCs) in type I IFN production and development of UVB irradiation–induced inflammation. Methods Mice were irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 34 publications
8
67
1
Order By: Relevance
“…Consistent with activation of the cGAS-STING pathway and failure to detect pDC in short term experiments (Sontheimer et al, 2017) and confirmed here (not shown), exposure to UVB light triggered an early increase in the circulating levels of IFNβ in WT mice ( Fig. 3D).…”
Section: Skin Exposure To Uvb Light Triggers a Systemic Ifn-i Responsesupporting
confidence: 87%
See 4 more Smart Citations
“…Consistent with activation of the cGAS-STING pathway and failure to detect pDC in short term experiments (Sontheimer et al, 2017) and confirmed here (not shown), exposure to UVB light triggered an early increase in the circulating levels of IFNβ in WT mice ( Fig. 3D).…”
Section: Skin Exposure To Uvb Light Triggers a Systemic Ifn-i Responsesupporting
confidence: 87%
“…How photosensitivity leads to systemic disease exacerbations in SLE is unknown. We previously showed that repetitive exposure of mice to low doses (100 mJ/cm 2 ) of UVB light triggered IFN-I response in the skin (Sontheimer et al, 2017), a result recently confirmed by Wolf et al . However, we observed that expression of type I interferon (IFN-I) signature genes (ISG) in the skin was blunted in mice deficient in the DNA sensing adapter, STING (stimulator of interferon genes) (Sontheimer et al, 2017).…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations